Perilaku Dan Keamanan Bendungan Manggar, Kalimantan Timur - Carlina Soetjiono (JURNAL SUMBER DAYA AIR, 2010)
A safety evaluation of the Manggar dam in East Kalimantan has been carried out based on a combination of field inspection, instrument evaluation from 2004 to 2007 and a slope stability analysis during the research program of the year 2008. The results of the evaluation are then presented in the form of total risk index (IRtot) and dam safety value (Naman). The Manggar dam has a total risk index (IRtot) of 20,18 and a dam safety value (Naman) of 76,80, which meant that the dam was in a satisfied condition. The stability analysis presents that the upstream and down stream of dam was stable in a normal condition as well as in an abnormal (flood and earthquake) condition, so that there is no needs for further action of improvement of investigation as well as design and construction of the dam.